2016
DOI: 10.1002/anie.201508622
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Highly Selective Photoredox C(sp2)−H Difluoroalkylation and Perfluoroalkylation of Hydrazones

Abstract: The first gold-catalyzed photoredox C(sp(2) )-H difluoroalkylation and perfluoroalkylation of hydrazones with readily available RF -Br reagents is reported. The resulting gem-difluoromethylated and perfluoroalkylated hydrazones are highly functionalized, versatile molecules. A mild reduction of the coupling products can efficiently produce gem-difluoromethylated β-amino phosphonic acids and β-amino acid derivatives. In mechanistic studies, a difluoroalkyl radical intermediate was detected by an EPR spin-trappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(80 citation statements)
references
References 78 publications
0
80
0
Order By: Relevance
“…is arylhydrazone anion acts as an electron-donating moiety in conjugation with the strong electron-deficient tricyanofuran moiety leading to an interesting spectral switch of a donor-acceptor molecular system under pH stimulus [24]. Figure 3 displays the UVvisible absorption spectra and color changes of dye 1 dissolved in acetonitrile (ca.…”
Section: Assessment Of Ph Sensing Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…is arylhydrazone anion acts as an electron-donating moiety in conjugation with the strong electron-deficient tricyanofuran moiety leading to an interesting spectral switch of a donor-acceptor molecular system under pH stimulus [24]. Figure 3 displays the UVvisible absorption spectra and color changes of dye 1 dissolved in acetonitrile (ca.…”
Section: Assessment Of Ph Sensing Effectmentioning
confidence: 99%
“…Hydrazones are originally a Schiff-base group of materials possessing a secondary amine proton comprising an important category of compounds in a diversity of research fields, such as nonlinear optics, sensors, and a variety of biological and medical applications [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…One of the very first reports on catalytic activity of gold nanoparticles covered hydrogenation . Considering photochemical catalysis, the effect of light excitation has been investigated with mono‐ and dinuclear gold(I) complexes . Regarding plasmonic catalysis, the effect of light excitation on the H 2 and D 2 exchange over Au/TiO 2 and Au/SiO 2 catalysts has been reported .…”
Section: Introductionmentioning
confidence: 99%
“…[56,57] Considering photochemicalc atalysis, the effect of light excitation has been investigated with mono-and dinuclearg old(I) complexes. [58][59][60][61][62][63] Regarding plasmonicc atalysis, the effect of light excitation on the H 2 and D 2 exchange over Au/TiO 2 and Au/SiO 2 catalysts has been reported. [46,47] In these examples, it has been demonstrated that localized surface plasmon resonance-excited hot electrons are able to facilitatet he H 2(g) splitting rate at the surface of the nanoparticles at room temperature when these materi-als are excited by green light.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Very recently, a new approach based on a gold-catalyzed C(sp 2 )-H phosphonyldifluoromethylation of hydrazone derivatives was reported by Hashmi and co-workers. [26] Taking benefit from the recent advances in photoredox catalysis, the astute combination of gold photocatalyst [Au(m-dppm) 2 ](OTf) 2 with UVA irradiation to form a phosphonodifluoromethylene radical, generated from BrCF 2 PO(OEt) 2 , furnished an efficient pathway toward the addition of such a phosphate mimic onto carbonyl derivatives. A large panel of hydrazine derivatives was efficiently functionalized with complete stereocontrol since only E isomers were synthesized.…”
Section: Photoredox Catalysismentioning
confidence: 99%